Annual Cover Crops in Florida Vegetable Systems Part 3. Buying and Sourcing - Danielle Treadwell; Waldemar Klassen; Michael Alligood; Stephanie Shewey (EDIS, 2008)
HS-1142, an 8-page illustrated fact sheet by Danielle Treadwell, Waldemar Klassen, Michael Alligood, and Stephanie Shewey, is part three of the three-part Annual Cover Crops in Florida Vegetable Systems series. It presents points to consider when purchasing cover crop seeds and provides contact information for cover crop seed retailers and wholesalers. Includes references and contact information for US retailers of cover crop seed and rhizobium inoculant. Published by the UF Department of Horticultural Sciences, March 2008.